1959
DOI: 10.1128/jb.78.4.500-505.1959
|View full text |Cite
|
Sign up to set email alerts
|

LOCALIZATION OFS-ADENOSYLMETHIONINE INCANDIDA UTILISBY ULTRAVIOLET MICROSCOPY

Abstract: Supplementation of the culture medium of Candida utilis (Torulopsis utilis) and of Saccharomyces cerevisiae with L-methionine results in greatly increased formation and accumulation of S-adenosylmethionine (Schlenk and DePalma, 1957a), a sulfonium compound whose structure comprises adenosine and methionine in the following way: Adenine-ribose-S-CH2 CH2 CH(NH2) C OOH &H3 Under suitable conditions, a concentration of 40 to 60 Amoles per gram of yeast cells on a dry weight basis may be obtained. Because the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1960
1960
2008
2008

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Of unusual interest was the amount of adenosylmethionine found in strain 10259 when cultured under nonsupplemented conditions. It was almost as much as that obtained in early experiments with C. utilis when methionine was used as a sulfur supplement (18).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Of unusual interest was the amount of adenosylmethionine found in strain 10259 when cultured under nonsupplemented conditions. It was almost as much as that obtained in early experiments with C. utilis when methionine was used as a sulfur supplement (18).…”
Section: Resultssupporting
confidence: 52%
“…Svihla and Schlenk (18) demonstrated that the presence of sulfur amino acids in a growth medium can inhibit the growth of S. cerevisiae and C. utilis. Supplementation of the growth medium with sulfur amino acids also inhibited the growth of C. albicans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The convincing demonstrations by Svihla and co-workers (26)(27)(28) that the ultraviolet microscope can be of considerable use in locating and following the fate of ultraviolet-absorbing substances in living cells provided impetus for the present study. The ability to measure ribonucleoprotein in the chromatoid bodies of living cells has enabled us to draw a much more precise picture of the changes in the concentration of RNA in the cells than has hitherto been possible.…”
Section: Introductionmentioning
confidence: 80%
“…Unlike most other microorganisms, yeasts accumulate large quantities of S-adenosylmethionine (7,18,21) when grown in the presence of methionine. The enzyme S-adenosylmethionine synthetase is present in yeast even when grown without exogenous methionine (16).…”
mentioning
confidence: 99%